NANS suppresses NF-κB signaling to promote ferroptosis by perturbing iron homeostasis - Ziyang Wang; Yuqin Di; Lvlan Ye; Wenzheng Fang; Xiangqiong Wen; Xiang Zhang; Jiale Qin; Youpeng Wang; Kunhua Hu; Zhenxin Zhu; Weiling He; Ying Chen (Cell Reports)
Summary: Metastatic colorectal cancer (CRC) cells endure survival challenges, including treatment-induced ferroptosis. While adaptation to ferroptosis stress facilitates metastasis, reciprocal regulatory mechanisms remain unclear. Here, a CRISPR-Cas9 screen identifies N-acetylneuraminate synthase (NANS) as a ferroptosis promoter in CRC, regardless of its metabolic function. NANS expression is downregulated and correlates with poor prognosis in patients with CRC. Under ferroptotic stress, cyclin-dependent kinase 1 (CDK1) phosphorylates NANS at serine 275 (S275), triggering its dissociation from TAK1. Phosphorylated NANS is ubiquitinated by UBE2N at K246, leading to degradation, which activates TAK1-NF-κB signaling and upregulates the ferroptosis inhibitor FTH1, enabling metastasis via ferroptosis resistance. NANS pS275 levels are associated with tumor aggressiveness and clinical outcomes in patients with CRC. These findings indicate that NANS suppresses CRC metastasis by enhancing ferroptosis susceptibility, while CDK1-mediated phosphorylation at S275 drives adaptive resistance. Targeting this phosphorylation axis may improve ferroptosis-inducing therapies to restrict metastatic progression in CRC.